2020
DOI: 10.1002/cnma.202000371
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Self‐Ordered Tantalum‐Niobium Mixed Oxide Nanotubes and Their Use for Clean Hydrogen Production

Abstract: We report on the first fabrication of vertically‐oriented tantalum‐niobium mixed oxide nanotube arrays (Ta−Nb−O NTs) via one‐step anodization of Ta−Nb alloy sheet in NH4F‐containing electrolytes. The synthesized Ta−Nb−O NTs were fully characterized via X‐ray diffraction (XRD), field‐emission scanning electron microscopy (FESEM), high‐resolution transmission electron microscopy (HRTEM), and X‐ray photoelectron spectroscopy (XPS). The prepared nanotubes have an average diameter of ∼35 nm with a wall thickness ∼1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Thus, to overcome the limitations, increase efficiency, and achieve the desired characteristics, extensive research is needed to design and develop efficient photoelectrodes. Among several metal oxide photoelectrodes, titanium dioxide (TiO 2 ) has some distinctive properties including high corrosion resistance, good charge transfer, being environmentally benign, and exceptional stability, validating its use in several applications, especially solar cells and photoelectrochemical water splitting. However, some obstacles are yet to be resolved, such as limited efficiency of light utilization and the short lifetime of the photogenerated e – /h + pairs which leads to fast carriers recombination that adversely affects its performance in solar-energy-based systems. ,, To this end, fabricating 1D nanostructured photoelectrodes (nanotubes, nanowires, and nanorods) could provide high surface area, ensuring fast charge transfer with limited carriers recombination. ,, In this sense, one of the best approaches to develop a diversity of 1D nanostructures is electrochemical anodization, which is an efficient and low-cost technique. ,, However, doping was shown to boost the catalytic activity of TiO 2 and improve its overall performance. However, serious problems originated from some doping approaches that consider the interactions between dopant and defects and hide the essential interactions between both dopant and lattice. Thus, the effective doping approach should include suitable elements with definite ratios, which are crucial for the resultant photoresponse. ,,, Some recent studies of 1D nanostructures of mixed oxides showed a great improvement in photoelectrochemical systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to overcome the limitations, increase efficiency, and achieve the desired characteristics, extensive research is needed to design and develop efficient photoelectrodes. Among several metal oxide photoelectrodes, titanium dioxide (TiO 2 ) has some distinctive properties including high corrosion resistance, good charge transfer, being environmentally benign, and exceptional stability, validating its use in several applications, especially solar cells and photoelectrochemical water splitting. However, some obstacles are yet to be resolved, such as limited efficiency of light utilization and the short lifetime of the photogenerated e – /h + pairs which leads to fast carriers recombination that adversely affects its performance in solar-energy-based systems. ,, To this end, fabricating 1D nanostructured photoelectrodes (nanotubes, nanowires, and nanorods) could provide high surface area, ensuring fast charge transfer with limited carriers recombination. ,, In this sense, one of the best approaches to develop a diversity of 1D nanostructures is electrochemical anodization, which is an efficient and low-cost technique. ,, However, doping was shown to boost the catalytic activity of TiO 2 and improve its overall performance. However, serious problems originated from some doping approaches that consider the interactions between dopant and defects and hide the essential interactions between both dopant and lattice. Thus, the effective doping approach should include suitable elements with definite ratios, which are crucial for the resultant photoresponse. ,,, Some recent studies of 1D nanostructures of mixed oxides showed a great improvement in photoelectrochemical systems.…”
Section: Introductionmentioning
confidence: 99%
“…7,11,15−19 To this end, fabricating 1D nanostructured photoelectrodes (nanotubes, nanowires, and nanorods) could provide high surface area, ensuring fast charge transfer with limited carriers recombination. 15,20,21 In this sense, one of the best approaches to develop a diversity of 1D nanostructures is electrochemical anodization, which is an efficient and low-cost technique. 9,10,22−26 However, doping was shown to boost the catalytic activity of TiO 2 and improve its overall performance.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many strategies were devoted to enhance the photocatalytic activity of TiO 2 to overcome the aforementioned limitations. To this end, nanostructuring the material in the form of nanowires, nanorods and nanotubes is favorable over the planar counterpart as that significantly enhances the light trapping and suppresses the electron‐hole recombination, while offering high surface area . Moreover, doping TiO 2 with the appropriate dopant is considered one of the most promising and outstanding approaches to tune the material bandgap, thus improving its performance in PECs.…”
Section: Introductionmentioning
confidence: 99%
“…However, anodization is an easy and low-cost method of fabrication [16,17]. TNTs made by anodization are more attractive due to theirs larger surface area, dielectric behavior, band gap shrinkage and ordered morphology [18,19]. Its indirect bandgap is about 3.2-3.4 eV; however, shrinkage and shallowness of the bandgap depend upon the fabrication method and reduction of oxygen concentration [20,21].…”
Section: Introductionmentioning
confidence: 99%